CURRICULAR FLEXIBILIZATION AND ITS REFLECTIONS IN PRACTICE AND IN THE SCHOOL ENVIRONMENT FOR INCLUSIVE EDUCATION - Santos, Maylan Barbosa; Cruz, Lilian Moreira (Revista de Estudos em Educação e Diversidade - REED, 2022)
School inclusion goes beyond public policies, and based on that, this research addresses the importance of curricular flexibility in basic education and its effects on pedagogical practices related to the process of inclusion of students with Disabilities, Global Disorder of Development and High Skills/Giftedness. The large enrollment of children in inclusive education has demanded changes in public policies and in the curricular structure, requiring compromise to make school units into inclusive environments. The objective is to analyze the adaptation or flexibilization of the curriculum in pedagogical practices for the access and learning of students, the target audience of Special Education, from the analysis of documents that guide inclusive education and the Pedagogical Political Project. The research approach used in this work was qualitative, based on field research carried out through observation and writing in logbooks that took place during the period of the mandatory Supervised Internship III, referring to pedagogical practices facing the school inclusion process. Thus, it is concluded that for the effectiveness of school inclusion it is necessary more than laws and structures, it is necessary to break paradigms and build emancipatory, democratic and flexible curricula.